Stages of modernity in perspective: Jane Austen’s Pride and prejudice and José de Alencar’s Senhora - Maria Eulália Ramicelli (Acta Scientiarum. Language and Culture, 2019)
In the nineteenth century, England was one of the countries with a decisive influence on the formation of modern bourgeois society. Brazil experienced this process very unevenly and in particular ways. Jane Austen’s fiction and José de Alencar’s urban novels formalize important aspects of this formative process for both bourgeois society and the accompanying mindset in England and in Brazil respectively. A comparison of Austen’s Pride and prejudice and Alencar’s Senhora reveals similarities and differences between the narratives which point to meaningful contextual aspects of the broader modernizing process. Analysis of the relationship between point of view and the protagonists in both novels reveals specific socio-cultural rationales that the readers of both Austen and Alencar were encouraged to follow. In this sense, comparative study of the novels also discloses less obvious aspects of the formation of the modern bourgeois mindset in their different but related national and socio-cultural contexts.